Distinguishing Characteristics of COVID-19-Associated Mucormycosis; a Case Series - Samimiardestani, Seyedhadi; Irani, Shirin; Hasibi, Mehrdad; Seyedahadi, Maral; Bastaninejad, Shahin; Firouzifar, Mohammadreza; Mohammadi Ardehali, Mojataba; Berijani, Sina; Erfanian, Reza; Kazemi, Mohammad Ali; Etemadi-Aleagha, Afshar; Rahimi, Abolfazl; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Since the emergence of COVID-19 pandemic, several articles have reported the co-existence of mucormycosis and COVID-19. This study aimed to distinguish the characteristics of COVID-19-associated rhinocerebral mucormycosis. Methods: In this case series, 18 patients with COVID-19-associated rhinocerebral mucormycosis and unique clinical manifestations and outcomes, who were referred to Amiralam Hospital, a tertiary otorhinolaryngology center, Tehran, Iran, during the COVID-19 era, were reported. Results: Eighteen patients with the mean age of 62.0 ± 11.6 (range: 42 – 83) years were studied (50% males). The mean time interval between diagnosis of COVID-19 and first manifestation of mucormycosis was 15.5 ± 9.7 days. The most common presenting symptom was facial paresthesia (72.2%). Fifty percent of patients developed frozen eye. Palatal necrosis was seen in 7 cases (38.8%). Remarkably, facial paralysis was observed in 5 (27.7%) patients. Another notable clinical picture was cavernous sinus thrombosis, seen in 7 patients. We also had two cases of carotid artery occlusion. Three patients, unfortunately, passed away. Conclusion: Rhinocerebral mucormycosis is one of the most important complications of COVID-19 patients, especially those with underlying diseases. It seems that the key to proper management of mucormycosis is early diagnosis and timely intervention, which could give a patient a chance to live more.